Absorbing TiOx thin film enabling laser welding of polyurethane membranes and polyamide fibers. Issue 5 (25th September 2015) - Amberg, Martin; Haag, Alexander; Storchenegger, Raphael; Rupper, Patrick; Lehmeier, Frederike; Rossi, René M; Hegemann, Dirk
Abstract: We report on the optical properties of thin titanium suboxide (TiO x ) films for applications in laser transmission welding of polymers. Non-absorbing fibers were coated with TiO x coatings by reactive magnetron sputtering. Plasma process parameters influencing the chemical composition and morphology of the deposited thin films were investigated in order to optimize their absorption properties. Optical absorption spectroscopy showed that the oxygen content of the TiO x coatings is the main parameter influencing the optical absorbance. Overtreatment (high power plasma input) of the fiber surface leads to high surface roughness and loss of mechanical stability of the fiber. The study shows that thin substoichiometric TiO x films enable the welding of very thin polyurethane membranes and polyamide fibers with improved adhesion properties.